2011
DOI: 10.1086/660861
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Insurance and Low-Educated, Single, Working Mothers before and after Welfare Reform

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our findings suggest that adoption of the ABP to increase levels of monetary eligibility alone may not be an effective strategy for raising UI recipiency rates among low‐educated or low‐earning workers, broadly. This implication is consistent with previous work that has suggested that nonmonetary eligibility requirements and rates of application may be important barriers to UI access for the broad group of low‐earning unemployed workers (Gould‐Werth & Shaefer, ; Holzer, ; O'Leary & Kline, ; Rangarajan, Razafindrakoto, & Corson, ; Shaefer & Wu, ). Our findings suggest further policy change would be necessary to substantially expand UI coverage for the broad group of low‐educated unemployed workers.…”
Section: Interpretation Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings suggest that adoption of the ABP to increase levels of monetary eligibility alone may not be an effective strategy for raising UI recipiency rates among low‐educated or low‐earning workers, broadly. This implication is consistent with previous work that has suggested that nonmonetary eligibility requirements and rates of application may be important barriers to UI access for the broad group of low‐earning unemployed workers (Gould‐Werth & Shaefer, ; Holzer, ; O'Leary & Kline, ; Rangarajan, Razafindrakoto, & Corson, ; Shaefer & Wu, ). Our findings suggest further policy change would be necessary to substantially expand UI coverage for the broad group of low‐educated unemployed workers.…”
Section: Interpretation Of Resultssupporting
confidence: 91%
“…Many employers in the food service and retail sectors, for example, follow a practice termed “work loading,” which keeps employees on the payroll but reduces scheduled hours, sometimes to zero, so that formal layoff is avoided (Lambert, ). A number of existing studies suggest that nonmonetary requirements may be the key eligibility barrier to UI access for unemployed workers with low earnings or short or sporadic work histories (Holzer, ; O'Leary & Kline, ; Rangarajan, Razafindrakoto, & Corson, ; Shaefer, ; Shaefer & Wu, ).…”
Section: Introductionmentioning
confidence: 99%
“…When considered alongside patterns in UI receipt, these findings indicate that some workers face multiple barriers when accessing the program. For example, in addition to being less likely to meet monetary eligibility criteria, as demonstrated in this paper, prior studies have shown that female workers, less-educated workers, and part-time workers are less likely to meet non-monetary criteria (Shaefer, 2010;Shaefer & Wu, 2011). Female workers may be excluded from UI at higher rates because their reasons for exiting employment do not qualify as good cause (e.g., quitting a job to take up family care responsibilities) (Um'rani & Lovell, 2000).…”
Section: Discussionmentioning
confidence: 75%
“…Although monetary criteria help to balance program inclusivity with program size and costs, they may create barriers for some groups of workers. Existing studies of access to UI among the unemployed find lower rates of UI receipt among women (Chan, et al, 2014;Michaelides & Mueser, 2012), Hispanic and non-white workers (Chan, et al, 2014;Michaelides & Mueser, 2012), younger workers (Chan, et al, 2014;Michaelides & Mueser, 2012;Vroman, 2009), less-educated low-wage workers (Chan, et al, 2014;GAO, 2000;Shaefer, 2010), former welfare recipients (Shaefer & Wu, 2011;Turner, Danziger, & Seefeldt, 2006), non-citizens (Gould-Werth & Shaefer, 2012, and part-time workers (Chan, et al, 2014;GAO, 2000;Vroman, 1998Vroman, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Shaefer and Wu () examine the participation of low‐educated, single working mothers both before and after welfare reform. They find that the UI has become a more common form of cash assistance than welfare for this group of women, even though UI benefit receipt levels did not change vis‐à‐vis low‐educated but childless women.…”
Section: Social Insurance Programsmentioning
confidence: 99%